The Influence of Board’s Educational Background on Indonesian Top Firms Profitability - Jeremy Surya Wijaya; Anthony Steven Setiawan; Anthonius Brandon Yuwono; Abel Yudo Prakoso (Indonesian Business Review, 2022)
This paper aims to observe the implications of higher education on firm performance based on a financial indicator that is most likely depicts the expertise of board members to utilize given assets to generate revenue. This paper will analyze both of board of commissioners and board of directors on Indonesian companies that have been consistently listed among the top 100 companies based on market capitalization during the period of observation which is 2010-2018. The education data of said Board of Commissioners or BOC and Board of Directors or BOD will be collected and analyzed to see how well they affect the ROA. It can be noted that only MBA degree on the BOC and doctoral degree on BOD does indeed have a significant positive correlation. It can be concluded that the managerial skills do help BOC to give advices and strategies that would help the firm performance, and the specialized expertise in the form of doctoral degree might give an edge to the directors to help them during day to day operations.